In-Law Preferences in China and in Cyprus: Differences and Similarities - Yan Wang; Menelaos Apostolou (Evolutionary Psychology, 2017)
Across different times and cultures, parents exercise considerable influence over their children’s mate choices. When they do so, parents are looking for specific traits in a prospective daughter- and son-in-law. Using a sample of 674 parents, the current research investigated in-law preferences in China. Participants rated 88 different traits, which were clustered in 10 different preference domains. In-law preferences were found to be contingent on the sex of the in-law and the sex of the parent. The data from the current study were compared with data from a different study which took place in the Republic of Cyprus. It was found that preferences varied in the two samples, but specific cultural differences were identified. It was also found that for both samples, the 10 different domains clustered in two supra-domains. The first supra-domain, where personality traits clustered, was preferred more by both Chinese and Greek-Cypriot parents than the second domain, where the rest of the traits clustered.